Effect of Structured Parental Education on Parental Support and Quality of Life of Children with Thalassemia in Indonesia: A Quasi-Experimental Study - Wuri Utami; Mohd Nazri; Khalid Bin Mokti; Putra Agina Widyaswara Suwaryo (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Thalassemia is a lifelong hereditary blood disorder that requires continuous treatment and family involvement. Parents play an important role in supporting medical adherence and emotional stability in affected children. However, limited knowledge and coping difficulties may reduce the consistency and quality of parental support. This study explored whether a structured parental education program based on the Health Belief Model could improve parental support and children’s quality of life. Methods: A quasi-experimental pretest–posttest control group design was used. Fifty-six parents of children with thalassemia were included and divided into an intervention group (n = 28) and a control group (n = 28). Participants were recruited through random sampling at a regional referral hospital between June and December 2023. The intervention involved structured face-to-face education sessions addressing disease information, emotional support strategies, communication skills, and home care practices. Parental support was measured using a validated multidimensional questionnaire, and children’s quality of life was assessed with a standardized instrument. Data were analyzed using Wilcoxon Signed-Rank and Mann–Whitney tests with a significance level of p < 0.05. Results: After six weeks, parental support scores increased in the intervention group from a median of 31.50 to 37.00 (p < 0.001), while the control group showed no significant change (p = 0.069). Children’s quality of life scores also improved significantly in the intervention group compared with the control group (p < 0.001). The magnitude of improvement was greater among parents who received the educational program. Conclusion: Structured parental education was associated with improved parental support and better quality of life in children with thalassemia. Integrating parent-focused education into routine care may strengthen family involvement and support more holistic management of chronic conditions.